Successful Management of Early Cervical Ectopic Pregnancy with Single Dose Methotrexate (Delta Medical College Journal, 2024)
Cervical ectopic pregnancy is an uncommon but a potentially life-threatening condition due to risk of severe haemorrhage and occasional need of hysterectomy. Transvaginal ultrasonogram is a key way to diagnose such a case. Early detection and conservative approach of treatment could limit the morbidity and preserve fertility in many cases. Here, we present a case of cervical pregnancy diagnosed by ultrasonogram at 6 weeks of gestation and treated successfully by a single dose of intramuscular methotrexate.Delta Med Col J. Jan 2021;9(1):58-61